Demonstration of rewritable hologram by using photo-induced optical nonlinearity in liquid crystals. (21st November 2020) - Miyagawa, Minako; Sohn, Woon Yong; Katayama, Kenji
Abstract: The photo-responsive liquid crystals (LCs) close to the isotropic condition shows very large optical nonlinearity lasting for tens/hundreds of milliseconds after a pulse light illumination due to the flow-induced reorientation of liquid crystals. By optimizing the temperature and the pump light intensity, we succeeded to demonstrate various refractive index patterns due to this optical nonlinearity with a pattern illumination under a microscope. We demonstrated a rewritable hologram by using a computer generated hologram pattern on a photo-responsive LC.